2007
DOI: 10.1093/carcin/bgm248
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin downregulates the inflammatory cytokines CXCL1 and -2 in breast cancer cells via NFκB

Abstract: The dietary antioxidant Curcumin has been proposed for cancer chemoprevention since it induces apoptosis and inhibits the formation of breast cancer metastases. Curcumin acts through the inhibition of phosphorylation of the inhibitor of kappa B (IkappaB), which in turn reduces the nuclear translocation of nuclear factor kappa B (NFkappaB), an inflammation- and cell survival-related transcription factor. However, it is not clear whether the strong antimetastatic effect can exclusively be explained by inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
156
1
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(172 citation statements)
references
References 38 publications
7
156
1
8
Order By: Relevance
“…EGFR is overexpressed in numerous types of head and neck cancer, and molecular therapies targeting the EGFR/AKT signaling cascade the therapeutic efficacy of standard platinum-based chemotherapy (90). In addition, the expression levels of multiple NF-κB-regulated gene products, including IL-6, IL-8, MMP-9, COX-2, CCL2 and Bcl-XL, were reduced (86,(91)(92)(93)(94)(95).…”
Section: Head and Neck Cancermentioning
confidence: 99%
“…EGFR is overexpressed in numerous types of head and neck cancer, and molecular therapies targeting the EGFR/AKT signaling cascade the therapeutic efficacy of standard platinum-based chemotherapy (90). In addition, the expression levels of multiple NF-κB-regulated gene products, including IL-6, IL-8, MMP-9, COX-2, CCL2 and Bcl-XL, were reduced (86,(91)(92)(93)(94)(95).…”
Section: Head and Neck Cancermentioning
confidence: 99%
“…Bachmeier et al (25) and Killian et al (26) reported that curcumin prevents NF-ĸB activation by inhibiting phosphorylation and degradation of IĸBα. Curcumin is also shown to inhibit the activation of p65 (one of the NF-ĸB transcription factor family) in estrogen receptor (ER)-negative breast cancer cells (25) and in prostate cancer cells (26).…”
Section: Potential Anti-migration Anti-invasion and Anti-colony Formmentioning
confidence: 99%
“…Bachmeier et al (25) and Killian et al (26) reported that curcumin prevents NF-ĸB activation by inhibiting phosphorylation and degradation of IĸBα. Curcumin is also shown to inhibit the activation of p65 (one of the NF-ĸB transcription factor family) in estrogen receptor (ER)-negative breast cancer cells (25) and in prostate cancer cells (26). Singh et al showed that curcumin inhibits NF-ĸB activation pathway in the signal transduction cascade of NF-ĸB activation before the IĸBα phosphorylation but after the point at which signals transduced by various stimuli converge (27).…”
Section: Potential Anti-migration Anti-invasion and Anti-colony Formmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, curcumin inhibited migration of MDA-MB-231 cells through the down regulation of protein expression of the transcription factor, NFκB (Chiu & Su, 2009). Lastly, curcumin also reduced the expression of the two prometastatic cytokines, CXCL1 and -2, which in turn reduces expression of the chemotactic receptor CXCR4 along with other metastasispromoting genes (Bachmeier et al, 2008). The anti-metastatic effect of curcumin has also been studied in various in vivo models.…”
Section: Curcuminmentioning
confidence: 99%